Empirical mode decomposition of local field potential data from optogenetic experiments - Oprisan, Sorinel A.; Clementsmith, Xandre; Tompa, Tamas; Lavin, Antonieta (Frontiers in Computational Neuroscience, 2023)
This study investigated the effects of cocaine administration and parvalbumin-type interneuron stimulation on local field potentials (LFPs) recorded in vivo from the medial prefrontal cortex (mPFC) of six mice using optogenetic tools. The local network was subject to a brief 10 ms laser pulse, and the response was recorded for 2 s over 100 trials for each of the six subjects who showed stable coupling between the mPFC and the optrode. Due to the strong non-stationary and nonlinearity of the LFP, we used the adaptive, data-driven, Empirical Mode Decomposition (EMD) method to decompose the signal in orthogonal Intrinsic Mode Functions (IMFs). Through trial and error, we found that seven is the optimum number of orthogonal IMFs that overlaps with known frequency bands of brain activity. We found that the Index of Orthogonality (IO) of IMF amplitudes was close to zero. The Index of Energy Conservation (IEC) for each decomposition was close to unity, as expected for orthogonal decompositions. We found that the power density distribution versus frequency follows a power law with an average scaling exponent of approximately 1.4 over the entire range of IMF frequencies 2-2000 Hz. The scaling exponent is slightly smaller for cocaine than the control, suggesting that neural activity avalanches under cocaine have longer life spans and sizes.